Well leg compartment syndrome in trauma surgery – femoral shaft fracture treated by femoral intramedullary nailing in the hemilithotomy position: case series and review of the literature - Brouze IF; Steinmetz S; McManus J; Borens O (Dove Medical Press, 2019)
Iris F Brouze, Sylvain Steinmetz, John McManus, Olivier BorensService of Orthopaedic surgery and Traumatology, CHUV – University Hospital Vaud, Lausanne, SwitzerlandAbstract: Well leg compartment syndrome (WLCS) is a rare complication which can occur following urological, gynecological, general surgical or orthopaedic surgeries carried out with the lower limb in the hemilithotomy position. WLCS is associated with significant morbidity and mortality because delay in diagnosis and treatment can lead to loss of function and even life-threatening complications. During orthopaedic surgeries on a traction table, such as femoral nailing, the contralateral “well leg” is often placed in the hemilithotomy position, thus facilitating the use of fluoroscopy. This position (also named the Lloyd-Davis position) consists of hip flexion, abduction, external rotation and knee flexion. We present the cases of two teenaged patients who underwent femoral nailing on an extension table of a femoral fracture and developed WLCS. We also present a review of the literature and a discussion of the pathophysiology, risk factors and treatment of this condition. Clinicians need to be aware of the risk factors for WLCS and have high index of suspicion. Further studies looking at the risks, benefits and feasibility of ways to reduce this risk are required.Keywords: WLCS, well leg compartment syndrome, femoral shaft fracture, intramedullary nailing, hemilithotomy position, case series